Проблеми кадрової політики судової влади - Москвич, Л.; Moskvich, L. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2013)
У статті висвітлено проблеми кадрової політики судової влади в умовах сьогодення побудови правової держави. Обумовлено питання про створення об’єктивних та прозорих умов для підготовки й формування кадрів судової влади, що є одним із найважливіших завдань у межах судової реформи. Проаналізовано питання вдосконалення кадрового складу суддівського корпусу. Обґрунтовано окремі пропозиції щодо вдосконалення чинного законодавства у сфері кадрової політики судової влади.The article is devoted to the problems of personnel policy of judicial branch in the modern condition of the legal state. The key questions about the creation of objective and transparent conditions on preparation and forming personnel policy of judicial power that is one of the major tasks within the limits of state judicial reform are grounded. The questions of improvement of personnel composition of judges are analyzed. The separate suggestions concerning the improvement of current legislation in the area of personnel policy of judicial power are highlighted. The suggestions about practicability of introduction of additions to current national legislation about the judicial system and status of judges with the purpose of increase of both professionalism of judges and efficiency of court in the state judicial system are introduced.
The Problems of the Personnel Policy of the Judiciary.
Keywords: кадрова політика; судова влада; судоустрій; personnel policy; judiciary; judicial system